The Development of Borad game “The Adventure Of Algebra” in The Senior High School Mathematics Learning - Andini, Mei; Yunianta, Tri Nova Hasti (Al-Jabar: Jurnal Pendidikan Matematika, 2018)
Algebra has an important meaning in Senior High School learning. It needs to be combined by the interesting practice questions, with that reason, this research will develop a board game learning media that can be used in Algebra learning. The research aims to develop a board game learning media that is valid, practical, and effective as a means of training questions in Algebraic material. The research uses the ADDIE development model which consists of steps Analyze, Design, Development, Implementation, and Evaluation. This media is a set of the modified game from monopoly games. This media is named The Adventure Of Algebra, and has been tested on 34 class VIII C students of SMP Negeri 1 Ambarawa. The instruments of data collection technique in the research consisted of instruments for validating material and media aspects, practicality assessment instruments, student opinion instruments, and posttest pretest instruments. The Media of  board games have been declared valid from the aspect of material experts with a score of 95% and valid from media experts with a score of 96%, both of which are very good categories. The results of practicality assessment get a score of 90% in the very good category. The results of the pair t-test data that show the sig value. (2-tailed) produced from the pretest and posttest data is written 0,000 which means that the significance value is close to zero which is less than 0.05 with the posttest average value (67) higher than the average pretest (50.5). So that the media is effective to be used as a means of training Algebra questions at the junior high school level.